Development, characterization, and cross-amplification of 16 microsatellite primers for Atriplex tatarica (Amaranthaceae) - Kondrysová, Eva; Krak, Karol; Mandák, Bohumil (Applications in plant sciences, 2017)
PREMISE OF THE STUDY: Microsatellite primers were developed to characterize the genetic diversity and structure of the annual herb Atriplex tatarica (Amaranthaceae) and to facilitate ecological and evolutionary studies of A. tatarica and its relatives. METHODS AND RESULTS: Sixteen novel microsatellite primers were developed for A. tatarica based on high-throughput sequencing of enriched libraries. All markers were polymorphic, with the number of alleles per locus ranging from three to 25 and observed and expected heterozygosity ranging from 0.08 to 0.74 and 0.10 to 0.87, respectively. In addition, some of these loci were successfully amplified and showed polymorphisms in four Atriplex and seven Chenopodium species. CONCLUSIONS: The microsatellite markers published here will be useful in assessing genetic diversity, structure, and gene flow within and across populations of A. tatarica, as well as in other species of Atriplex and the related genus Chenopodium.
Keywords: Amaranthaceae; Chenopodium; microsatellites; cross-amplification; Atriplex